Lip repositioning for the treatment of gummy smile. Literature review - Arroyo Carbajal, Natalí (2019)
Today's patients demand an attractive or pleasing smile that is not embarrassing to express. Currently, people give great importance to physical beauty, since it is the reflection of one's identity. Different factors affect the smile and aesthetics, including the color, shape and position of the tooth, especially the anterior teeth. Excessive gummy smile is considered within the classification of the American Academy of Periodontology (AAP) as a clinical condition in which the gingiva is exposed (> 2 mm) when smiling. The manifestation of the gummy smile has different etiologies, including dental, skeletal, soft tissue factors and the combination of them. For its management, a good diagnosis and etiology must be established in order to determine the best treatment option among the various techniques described in the literature. The lip repositioning technique seems to be a good alternative since the treatment has shown stable results. It is achieved when a strip of maxillary labial mucosa is removed and then the labial mucosa is sutured to the mucogingival line. It is less traumatic, with few postoperative complications and rapid recovery, which is why it manages to satisfy the aesthetic requirements of the patient. The main objective of this article is to know the current considerations for the lip repositioning technique used as a treatment for gummy smiles and to analyze the result it generates in patients who undergo a change to improve their aesthetics and self-esteem.